Implementation of RFID Middleware Based on Client-Multiserver Architecture for Traceability of Autoparts (2019)
The implementation of RFID systems allows automation of information flow along the production chains. This is a desirable condition for increasing efficiency, productivity and management, and it simplifies other activities such as traceability records along these supply and production chains, especially in the automobile assembly supply chain as in the case of Renault-SOFASA-Colombia, where the traceability of automotive parts is realized manually by means of mobile terminals, which is time consuming and laborious, with low automotive parts rate and high error rate. In this work, a RFID solution for the traceability of automotive parts in real time in Renault-SOFASA-Colombia is implemented, where a middleware under client-multiserver architecture for Siemens readers is developed. The terminal, where the middleware is located, behaves like a client and links to several RFID readers which behave like servers, forming a star type network topology. This architecture allows a cost reduction in the implementation and operation of RFID solutions by reducing hardware acquisition and energy consumption, being an alternative that can compete with the solution provided by a manufacturer as Siemens without neglecting the robustness and the proper functioning of the system. Moreover, the proposed solution concentrates all the maintenance efforts of the system at a single point, which is due to the fact that a terminal attends all RFID portals. The tests performed, where the transport carts with the automotive parts and their respective RFID tags are passed through the RFID portals of the assembly plant, are in agreement with the results reported by the developed middleware. © 2003-2012 IEEE.